Kinematic comparison of team handball throwing with two different arm positions - Wagner, H.; Buchecker, M.; von Duvillard, S. P.; Müller, E. (International Journal of Sports Physiology and Performance, 2010)
Purpose: The aims of the present study were: (1) to compare the differences in the ball release speed and throwing accuracy between the ABOVE and SIDE throw; (2) to analyze kinematic differences of these two throwing techniques; and (3) to give practical applications to team handball coaches and players. Methods: Ball release speed, throwing accuracy, and kinematics were measured via the Vicon MX 13 (Vicon Peak, Oxford, UK) from 12 male elite right-handed team handball players. Results: Results of our study suggest that the two throwing techniques differ significantly (P < .0073) in the angles and/or angular velocities of the trunk (flexion, left tilt and rotation) and shoulder (flexion and abduction) of the throwing arm that result in a significantly different ball release speed (1.4 ± 0.8 m/s; P < .001) and that throwing accuracy was not significantly different. Conclusion: Our results indicated that the different position of the hand at ball release of the ABOVE and SIDE throws is primarily caused by different trunk flexion and tilt angles that lead to differences in ball release speed but not in throwing accuracy, and that the participants try to move their throwing arm similarly in both throwing techniques.